2012
DOI: 10.1007/s11051-012-1181-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MWCNT surface and chemical modification on in vitro cellular response

Abstract: The aim of this study was to evaluate the impact of multi-walled carbon nanotubes (MWCNTs with diameter in the range of 10–30 nm) before and after chemical surface functionalisation on macrophages response. The study has shown that the detailed analysis of the physicochemical properties of this particular form of carbon nanomaterial is a crucial issue to interpret properly its impact on the cellular response. Effects of carbon nanotubes (CNTs) characteristics, including purity, dispersity, chemistry and dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 54 publications
5
42
0
Order By: Relevance
“…The presence of high amounts of MWCNTs‐COOH inside cells in big cytoplasmic vesicles confirms the high cell uptake for carboxylated MWCNTs observed in our previous study (Ursini et al ., ) and is in agreement with the studies of Fraczek‐Szczypta et al . () and Zhang et al (). The higher uptake of COOH‐functionalized MWCNTs and their accumulation into cytoplasm could also explain the high inflammatory response found in A549 cells after 24‐h exposure to such CNTs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The presence of high amounts of MWCNTs‐COOH inside cells in big cytoplasmic vesicles confirms the high cell uptake for carboxylated MWCNTs observed in our previous study (Ursini et al ., ) and is in agreement with the studies of Fraczek‐Szczypta et al . () and Zhang et al (). The higher uptake of COOH‐functionalized MWCNTs and their accumulation into cytoplasm could also explain the high inflammatory response found in A549 cells after 24‐h exposure to such CNTs.…”
Section: Discussionmentioning
confidence: 94%
“…Higher cytotoxic and genotoxic effects for the functionalized MWCNTs were found in some studies (Magrez et al ., ; Coccini et al , ; Patlolla et al ., ; Zhang et al ., ). Otherwise other studies demonstrated that the ‐COOH functionalization process decreases MWCNTs toxicity (Fraczek‐Szczypta et al ., , Hamilton et al, , Liu et al , , Visalli et al , ). Pulmonary toxicity and an inflammatory response after exposure to pristine and ‐NH 2 and ‐COOH functionalized MWCNTs were found in vivo in rats (Roda et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have tackled this problem suggesting negative influence on cell culture and living organisms [36][37][38], though an agreement was not achieved in this matter. What should be noted is the fact that numerous researchers claim that functionalised MWCNTs are less toxic and only slightly affect cells viability [39][40][41].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Another study showed that MWCNTf induced a reduced cytotoxicity but a slight increase of inflammation and oxidative stress (Zhang et al 2012). Lastly, based on Fraczek-Szczypta et al work (Fraczek-Szczypta et al 2012), the cytotoxicity of MWCNTf remains globally unchanged compared to pristine MWCNT while they have a tendency to decrease cell proliferation.…”
Section: Introductionmentioning
confidence: 96%